Desenvolvimento de Processo de Produção de Biolubrificantes a Partir do Óleo de Soja, Integrado à Produção Industrial de Biodiesel - Parente Júnior, Expedito José de Sá (2018)
The biodiesel industry is the Brazilian industrial sector with the fastest growth in the last ten years. According to dozens studies, thousands of jobs were generated, millions tons of GHG emission were avoided, almost one hundred thousand of agriculture families were benefited by feedstock demand, Public health was enhanced in big city by improving air quality, among other benefits. However, the national biodiesel industry is traditionally idle. Almost forty biodiesel plants closed their activities in Brazil due to lack of competitiveness. Those that currently operate depend on strong fiscal incentives and market reserve brought by the mandatory mixes. Among them, there is no possibility for value differentiation. The competitiveness of biodiesel and the enhancement of its positive socio-environmental externalities will be achieved especially by the value aggregation of co-products and by the integration with the oleochemical industry, such as biolubricants, a product of growing demand in Brazil and abroad. There are several routes of production of lubricants from chemically modified vegetable oils. The epoxidation followed by oxirane ring opening has proved to be very versatile for the production of a portfolio of products with a wide range of physicochemical and performance properties, depending on the nature of functional group inserted in the molecule. Soybean is the main oilseed in Brazil and, therefore, the main raw material for the production of biodiesel and biolubricants. Soybean oil, because it is rich in polyunsaturated fatty acids, offers a greater amount sites for epoxidation, increasing the combinations of possible molecules to be obtained. In this work the synthesis of a set of biolubricants from soybean biodiesel was studied. Water, 2-ethylhexanol and their mixtures were used as reactants at the oxirane ring opening reactions in order to produce hydroxyl-rich molecules or ether-type branching, respectively, and to assess the impact of the differences in the chemical nature of these molecules on their physicochemical properties (viscosity, viscosity index, specific mass and pour point). From the laboratory essays, a proposal of industrial process of production of biolubricants was presented, being composed by 17 processes and unit operations, of which 11 can be integrated with the existing biodiesel plant. The work showed that the integration with the biodiesel industry can be an important artifice to facilitate the penetration of biolubricants in the market, while the integration with the biolubricant industry appears to be an important strategy to accelerate the economic competitiveness of biodiesel.